Responses of rhizosphere fungi to the root economics space in grassland monocultures of different age - Hennecke, Justus; Bassi, Leonardo; Mommer, Liesje; Albracht, Cynthia; Bergmann, Joana; Eisenhauer, Nico; Guerra, Carlos A.; Heintz‐Buschart, Anna; Kuyper, Thomas W.; Lange, Markus; Solbach, Marcel Dominik; Weigelt, Alexandra (The New phytologist, 2023)
Recent studies on root traits have shown that there are two axes explaining trait variation belowground: the collaboration axis with mycorrhizal partners and the conservation (‘fast – slow’) axis. However, it is yet unknown whether these trait axes affect the assembly of soilborne fungi. We expect saprotrophic fungi to link to the conservation axis of root traits, whereas pathogenic and arbuscular mycorrhizal fungi link to the collaboration axis, but in opposite directions, as arbuscular mycorrhizal fungi might provide pathogen protection. To test these hypotheses, we sequenced rhizosphere fungal communities and measured root traits in monocultures of 25 grassland plant species, differing in age. Within the fungal guilds, we evaluated fungal species richness, relative abundance and community composition. Contrary to our hypotheses, fungal diversity and relative abundance were not strongly related to the root trait axes. However, saprotrophic fungal community composition was affected by the conservation gradient and pathogenic community composition by the collaboration gradient. The rhizosphere AMF community composition did not change along the collaboration gradient, even though the root trait axis was in line with the root mycorrhizal colonization rate. Overall, our results indicate that in the long term, the root trait axes are linked with fungal community composition.